The Effectiveness of Rhythmic Gymnastics Through Video Zoom Cloud Meetings for Elementary School Students - Khavisa Pranata; Arum Fatayan; Sartika Ayu (Universitas Suryakancana, 2022)
This study aims to determine the effectiveness of learning rhythmic gymnastics using a zoom cloud meeting for elementary school students during the Covid-19 pandemic using the zoom cloud id application. The method used is a quantitative method with an experimental design used, namely a post-test only control design. The sampling technique used is saturated sampling. The sample in this study amounted to 61 students, consisting of 30 students in the experimental class and 31 students in the control class. The instrument test in this study used validity and reliability tests. There is a significant effectiveness of student learning outcomes in physical education subjects, rhythmic gymnastics learning materials using the zoom application media. This study uses data collection techniques in the form of questionnaires and documentation. The data analysis technique used in processing the data is the analysis prerequisite test including the normality and homogeneity test, and the final analysis is in the form of hypothesis testing, namely the effectiveness test (T-test). The results of the study show that learning with video conferencing is effective, interactive, can support distance learning, making it easier for students to absorb the learning material delivered by educators because it is more real time.Key words: Effectiveness; Rhythmic gymnastics; Zoom Cloud Meeting Videos